2020
DOI: 10.1038/s41598-020-65840-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of As(V) from aqueous media by magnetic nanoparticles prepared with Iron-containing water treatment residuals

Abstract: Two types of magnetic nanoparticles prepared with chemical agents (cMNP) and iron-containing sludge (iMNP), respectively, were synthesized by co-precipitation process and used to remove arsenate [As(V)] from water. The synthesized magnetic adsorbents were characterized by XRD, XPS, TEM, BET, VSM and FTIR. The adsorbents iMNP and cMNP were both mainly γ-Fe2O3 in nanoscale particles with the saturation magnetization of 35.5 and 69.0 emu/g respectively and could be easily separated from water with a simple hand-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Therefore, the adsorption kinetics of As 3+ and As 5+ from solution by the adsorbent Fe 3 O 4 @mZrO 2 -Re (Re = Y/La/Ce) is more suitably designated by the Pseudo-second-order reaction kinetic model, where rate of reaction depended directly on the square of the concentration of the reactants remaining in the solution [ 48 ]. Many other researchers suggested that adsorption kinetics of Magnetic nanomaterials are supporting the Pseudo-second order Kinetics, and our results are also favoring the 2nd order kinetic model [ 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 81%
“…Therefore, the adsorption kinetics of As 3+ and As 5+ from solution by the adsorbent Fe 3 O 4 @mZrO 2 -Re (Re = Y/La/Ce) is more suitably designated by the Pseudo-second-order reaction kinetic model, where rate of reaction depended directly on the square of the concentration of the reactants remaining in the solution [ 48 ]. Many other researchers suggested that adsorption kinetics of Magnetic nanomaterials are supporting the Pseudo-second order Kinetics, and our results are also favoring the 2nd order kinetic model [ 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 81%
“…Indeed, many magnetic Fe-oxide NP composites have been tested as As adsorbents in recent years [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Their adsorbent properties and experimental conditions are exposed and a comparison of their removal efficiency and an analysis of the experimental condition effects (pH, temperature, adsorbent dose, initial concentration, particle size and shape, surface area, and saturation magnetization, equilibrium time, kinetic and isothermal adsorption parameters) [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: In-detail Discussion Of the Adsorbent Propertiesmentioning
confidence: 99%
“…In a first phenomenological description of As adsorption processes, the Langmuir adsorption model is the most used one [ 42 , 60 , 64 , 65 , 70 , 75 ], while the Freundlich adsorption model can be considered as the second most applied [ 63 , 68 , 71 ] for both As(III) and As(V). For these reasons, it can be indirectly inferred that the monolayer adsorption mechanism is used more often than the multilayer adsorption.…”
Section: In-detail Discussion Of the Adsorbent Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several nanomaterials have been developed for contaminant remediation, such as nZVI, nanoscale zeolites, carbon nanotubes, metal oxides, bimetallic nanoparticles (BNPs), enzymes, and titanium dioxide (TiO 2 ) [52][53][54][55][56][57]. Soil remediation using these three nanoremediation materials (nZVI, TiO 2 , and CNTs) can be found in [58].…”
Section: Nanomaterialsmentioning
confidence: 99%